MODELS TO STUDY IN VITRO ANTIDIABETIC ACTIVITY OF PLANTS: A REVIEW - DORIN DSOUZA; N. LAKSHMIDEVI (International Journal of Pharma and Bio Sciences, 2015)
Antidiabetic effect of plants and their active principles can be assessed in vitro using a variety of biological test systems. They play a major role in evaluation of antidiabetic properties as an initial screening tool prior to in vivo studies. The present review focuses on in vitro assays that are available to study potential antidiabetic activity of plant extracts and their active constituents. It is evident that these plant extract and compounds derived from them are capable of lowering blood glucose level through different mechanism of action. This has attracted a great deal of research interest in exploring natural sources. In vitro assay provides a basic platform for accusing these plant extracts and help us understand various mechanisms that would alleviate hyperglycaemia in diabetes.